2016
DOI: 10.1007/s00268-016-3782-9
|View full text |Cite
|
Sign up to set email alerts
|

Handcrafted Vacuum‐Assisted Device for Skin Ulcers Treatment Versus Traditional Therapy, Randomized Controlled Trial

Abstract: Handcrafted vacuum-assisted system is a feasible and safe method to treat chronic ulcers. This system would benefit patients favoring earlier infection control, faster granulation tissue appearance and earlier discharge. Clinical trials registered in https://www.clinicaltrials.gov/ Number NCT02512159.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Based on the results of the literature search, several articles discussed NPWT. The first, second, and third articles focused on postoperative foot patients in the presence of surgical site infection (SSI) (Benrashid et al, 2020 ; Costa et al, 2020 ; Deborre et al, 2021 ), while the fourth, fifth, and sixth discussed NPWT for split skin grafts of diabetic foot ulcers on the wound healing process with a decrease in infection in vivo and in vitro (Gonzalez et al, 2017 ; Maduba et al, 2020 ; Seidel et al, 2020 ). Furthermore, the seventh article examined infection control in postoperative mastectomy patients (De Rooij et al, 2021 ), while the eighth reported vascular foot wound healing (Chiang et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of the literature search, several articles discussed NPWT. The first, second, and third articles focused on postoperative foot patients in the presence of surgical site infection (SSI) (Benrashid et al, 2020 ; Costa et al, 2020 ; Deborre et al, 2021 ), while the fourth, fifth, and sixth discussed NPWT for split skin grafts of diabetic foot ulcers on the wound healing process with a decrease in infection in vivo and in vitro (Gonzalez et al, 2017 ; Maduba et al, 2020 ; Seidel et al, 2020 ). Furthermore, the seventh article examined infection control in postoperative mastectomy patients (De Rooij et al, 2021 ), while the eighth reported vascular foot wound healing (Chiang et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The eighth article used a similar design with a total sample of n = 144 in diabetic ulcer patients with venous and arterial insufficiency for ten days, divided into the intervention ( n = 72) and the control group ( n = 72). The measuring instrument was wound assessment (Gonzalez et al, 2017 ). Furthermore, the ninth article used an RCT design on a total sample of n = 72 with post-infected complex injuries and divided into an intervention ( n = 36) and a control group ( n = 36).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted, however, that NPWT may provide other benefits beyond wound closure. For example, treatment with NPWT significantly reduced leukocyte count, pain, and systemic inflammatory response; discharge criteria and granulation tissue were also present significantly earlier when using this treatment [ 156 ]. Whether NPWT increases or decreases blood flow and oxygenation in treated tissues is controversial, as different investigative techniques have yielded varying results.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Los resultados fueron equiparables al del sistema comercial (8). Gonzales I et al (9) comparo terapia asistida por vacío comercial y artesanal en ulceras crónicas de miembro inferiores donde el recuento de leucocitos, la respuesta inflamatoria sistémica y el dolor fueron significativamente menor en el grupo tratado con el sistema artesanal (p < 0.05), así como también el tejido de granulación estuvo presente tiempo antes en el grupo artesanal (p < 0.05).…”
Section: Figura 6 Imagen Clínica Posterior a La Aplicación De Injerto...unclassified